Conceptual modeling : 35th International Conference, ER 2016, Gifu, Japan, November 14-17, 2016, Proceedings /: 35th International Conference, ER 2016, Gifu, Japan, November 14-17, 2016, Proceedings. ([2016]) - Unknown
No abstract available